Lao People's Democratic Republic : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report ;, 2007)
This Selected Issues paper and Statistical Appendix for the Lao People's Democratic Republic (PDR) review the macroeconomic impact of the resource sector. Lao PDR's economic performance is becoming increasingly dependent on the activities of the large mining and hydropower projects. The economic value of the resource projects is significant, even if only proven mineral reserves and hydropower plants are considered. The overall macroeconomic impact of the resource sector over the medium term will depend on the quality and timeliness of the policies adopted to sustain the growth of the non-resource sector.